A Compact and High-Power Rectenna Array for Wireless Power Transmission Applications - Dajiu Huang; Jincheng Li; Ziqiang Du; Changjun Liu; Zhongqi He; Ji Zhang (Energies)
Microwave wireless power transmission (MWPT) applications have attracted worldwide interest and attention in recent years. Rectennas are a crucial component of a MWPT system. The rectenna’s power capacity and output DC power have great significance with regard to the MWPT system’s performance. In this article, a compact 4 × 4 S-band rectangular patch rectenna array for MWPT is proposed and experimentally verified. Firstly, an S-band rectifier with better consistency and lower cost than a traditional output design using parallel capacitors as a filter is achieved. Then, a rectenna array based on the proposed rectifier and a novel design idea is proposed. The rectenna can achieve an output DC power of 117.6 mW/cm3 and an efficiency of 47.6%. Finally, a MWPT verification experiment is conducted. A 12-inch LCD screen powered by the rectenna with a rated power of 12 W successfully works without any other power supply. This article provides a new design of a rectenna for MWPT, and the proposed rectenna array demonstrates its good engineering significance and application prospects.